Social conflicts between actors in marine resource management in Palabuhanratu, West Java, Indonesia - Eva Royandi (Faculty of Social and Political Science, Universitas Airlangga, 2021)
Marine resources have become a niche of life for fishing groups on the coast of Palabuhanratu Sukabumi, West Java. The dependence of the fishing groups on natural resources has led to competition in the process of obtaining resources. The purpose of this study is to analyze stakeholders in marine resource management in Palabuhanratu. This research was conducted in Palabuhanratu, West Java, Indonesia. The research employed a qualitative approach with 60 informants, divided into 20 local fishermen, 20 migrant fishermen, and 20 external fishermen. The results of the study show several analyzes of the research objectives. First, several actors have an interest and influence in marine resource management in Palabuhanratu, including government actors, local fishermen, migrant fishermen, external fishermen, and marine tourism. Migrant fishermen have a high interest and influence in the process of exploiting marine resources in Palabuhanratu. Second, the relationships that exist between actors in the interaction process for the marine resource management in Palabuhanratu can take the form of negotiations and conflicts. Conflicts that occur are in the form of destroying other fishing gear, controlling the area, and protesting, while negotiations occur in the form of a cooperative relationship between groups of fishermen in catching fish and agreeing on boundaries for each type of fishing gear.